Arabic Language Learning Program Management of Madrasah Tsanawiyah Fadhilah Pekanbaru - Fitri, Ramadhaniati; Ajiji Lubis, Muhammad; Wahyudi, Hakmi (International Journal of Language and Ubiquitous Learning, 2023)
Background. This research was conducted to examine the effectiveness of Arabic language learning program management at Madrasah Tsanawiyah Fadhilah Pekanbaru. Focusing on the aspects of planning, organizing, implementing, and monitoring, the research aims to improve the quality of Arabic language learning and ensure conformity with the vision and mission of the madrasah. Purpose. The study aims to evaluate and improve the management of Arabic language learning program at Madrasa Tsanawiyah Fadhilah Pekanbaru. The focus is on optimizing the planning, organization, implementation, and supervision of the program to achieve effectiveness and efficiency in achieving the vision and mission of Arabic language education in the madrasah.. Method. This descriptive qualitative research aims to find out the management of the Arabic language program at MTs Fadhilah Pekanbaru. Data collection uses interviews with the principal, observation, and documentation about the management of Arabic language programs at madrasah tsanawiyah  Fadhilah Pekanbaru. Results. Madrasah Tsanawiyah  Fadhilah uses the functions of program management studies in implementing the Arabic language learning program for all students so that this program runs effectively and efficiently, namely: 1) Planning the Arabic language learning program in preschool children through the needs identification stage. 2) Organizing in this school is the coach as the head of the foundation who holds the highest power. 3) The implementation of the Arabic language learning program in preschool children is by preparing teachers, making learning process plans (RPP). Conclusion. The success of the Arabic language learning program at Madrasah Tsanawiyah Fadhilah Pekanbaru hinges on effective management functions. Consistency with the foundation's vision and mission is maintained through thorough planning, well-organized implementation, and direct supervision, highlighting the critical role of management in program success.